Direct evidence for interaction between human erythroid progenitor cells and a hemoglobin switching activity present in fetal sheep serum. - Stamatoyannopoulos, G (1983)
An activity that induces Hb F to Hb A switching in human cells is present in fetal sheep serum. To test directly the role of cell-to-environment interactions in hemoglobin switching and to define the level of erythroid cell differentiation at which this activity operates, colony transfer experiments were done. Clones grown in the presence of switching activity-containing medium (fetal sheep serum) or control medium (fetal calf serum) were transferred, at the 16- to 30-cell stage, to either fetal sheep serum or fetal calf serum plates and Hb F synthesis was determined in the fully mature erythroid bursts. Fetal calf serum-to-fetal calf serum transfers produced colonies with the high Hb F levels characteristic of undisturbed fetal calf serum-grown clones. Fetal sheep serum-to-fetal calf serum transfers resulted in significant decrease in Hb F synthesis, revealing an interaction between hemoglobin switching activity and cells at an early stage of progenitor cell development. The reduction of Hb F synthesis in fetal calf serum-to-fetal sheep serum transfers indicated that hemoglobin switching activity interacts with cells at later stages of progenitor cell development. Maximal decrease in Hb F synthesis was observed in fetal sheep serum-to-fetal sheep serum transfers, indicating that optimal effects on Hb switching are obtained when the environment that induces Hb switching is present throughout the development of progenitor cells. By splitting single early clones into two parts and transferring them to either a fetal sheep serum or a fetal calf serum environment, these interactions were further demonstrated in the progeny of a single erythroid burst-forming unit. Since all clone transfers were done on cell-free plates, the results of fetal calf serum-to-fetal sheep serum and of fetal sheep serum-to-fetal sheep serum transfers indicated that the switching activity does not require helper cells for its action. These studies show directly that (i) Hb F synthesis is controlled at the level of progenitors and (ii) it involves interactions between progenitor cells and their environment.